2022
DOI: 10.3390/gels8070398
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Friendly Bio-Hydrogels Based on Antheraea Pernyi Silk Gland Protein for Cell and Drug Delivery

Abstract: The Antheraea Pernyi silk gland protein originates from natural organisms and synthesized by tussah silk glands and has widely potential biomaterial applications due to the superior biocompatibility. This study investigates the Antheraea Pernyi silk gland protein-based drug-loaded bio-hydrogels for bioengineered tissue fabricated by using an eco-friendly method without the harsh extracting process and the usage of toxic chemicals. The drug-loaded bio-hydrogels exhibited a porous structure and interconnected po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…and free hydroxyl (−OH), along with ASGP, SA and PNIPAM, respectively [42,43]. According to the results of the FT-IR spectrum, the second derivative spectra and SEM, it is concluded that the abundant hydrogen bonds were formed between ASGP and SA, or ASGP and PNIPAM by the in situ polymerization method.…”
Section: Temperature Sensitivitymentioning
confidence: 97%
“…and free hydroxyl (−OH), along with ASGP, SA and PNIPAM, respectively [42,43]. According to the results of the FT-IR spectrum, the second derivative spectra and SEM, it is concluded that the abundant hydrogen bonds were formed between ASGP and SA, or ASGP and PNIPAM by the in situ polymerization method.…”
Section: Temperature Sensitivitymentioning
confidence: 97%
“…It is significant research value and application prospect that taking the fifth instar larvae of antheraea pernyi as the research object. In a previous study [26], we have investigated the possibility of Antheraea Pernyi silk gland protein/sodium alginate drug-loaded hydrogels with cell and drug delivery by composite coagulation bath including citric acid solution and CaCl 2 solution. In above paper, the bacteriostatic activity of bio-hydrogels was not investigated.…”
Section: Introductionmentioning
confidence: 99%